The relationship between Hemoglobin A1c and the maximal plaque stress of culprit ruptured plaques in patients with ST-segment elevated myocardial infarction. (1st July 2022) - Li, Jiannan; Chen, Runzhen; Zhou, Jinying; Wang, Ying; Zhao, Xiaoxiao; Liu, Chen; Zhou, Peng; Chen, Yi; Song, Li; Yan, Shaodi; Yan, Hongbing; Zhao, Hanjun
Abstract: Background: Plaque rupture occurs when the structural stress inside plaques exceeds the capacity of the overlying fibrous cap. Plaque structural stress has been acknowledged as an index to evaluate the risk of plaque rupture. However, impacting factors associated with the level of plaque structural stress in ST-segment elevated myocardial infarction patients with ruptured plaques remain unknown. Methods: Based on optical coherence tomography, we analyzed the plaque characteristics and calculated the maximal plaque stress of the culprit lesions in 162 patients with plaque rupture by performing finite element analysis. All enrolled patients were divided into two groups according to the level of maximal plaque stress. Cardiovascular risk factors, laboratory findings and clinical outcomes were compared between the two groups. Results: Hemoglobin A1c (HbA1c) was significantly higher in the high stress group than in the low stress group (7.0% ± 1.8 vs. 6.3% ± 1.2, p = 0.003). The maximal plaque stress of patients with diabetes was significantly higher than that of patients without diabetes (538.7 kPa [346.2–810.6] vs. 425.9 kPa [306.2–571.4], p = 0.006). Moreover, the level of maximal plaque stress was significantly associated with HbA1c (Pearson's correlation coefficient: r = 0.289, P < 0.001). OCT findings showed that the fibrous cap thickness and maximal lipid arc were significantly associated with maximal plaque stress ( r = −0.163, p = 0.038; r = 0.194, p = 0.013, respectively). Conclusion: OCT-based finite-element analysis showed that HbA1c was independently associated with the level of maximal plaque stress in STEMI patients with plaque rupture, thus indicating the importance of glucose control in patients with coronary atherosclerotic disease. Highlights: The first study to assess relationship of maximal plaque stress and cardiovascular risk factors in patients with plaque rupture based on optical coherence tomography. Patients with higher level of HAb1c exhibits higher maximal plaque stress. Maximal plaque stress is determined by fibrous cap thickness and maximal lipid arc.